Effects of two types of dietary fibre on faecal steroid and lipid excretion. Issue 5970 (7th June 1975) - Walters, R L; Baird, I M; Davies, P S; Hill, M J; Drasar, B S; Southgate, D A; Green, J; Morgan, B
Abstract : Fibre supplements from wheat bran and sugar cane residue (bagasse) were added to the normal diet of volunteers for 12-week periods in a controlled metabolic study. Stool weights and stool fat excretion increased on both dietary fibres. Bagasse increased the daily loss of acid steroids, but bran failed to affect bile acid excretion. Decreased transit time without alteration in faecal flora occurred with bagasse. The raised excretion of bile acids and fatty acids failed to lower the plasma cholesterol and triglycerides after 12 weeks. Thus different fibre sources with variable components have dissimilar metabolic effects.